Impact of ERCC2 Gene Polymorphisms on OSCC Susceptibility and Clinical Characteristics - Tejasvi, ML Avinash; Maragathavalli, Gopal; Kumar, Putcha Uday; Ramakrishna, M.; Raghavan, Vijaya; CK, Anulekha Avinash (Global Medical Genetics, 2020)
Background DNA repair systems play an important role in maintaining the integrity of the human genome. Deficiency in the repair capacity due to either mutations or inherited polymorphisms in DNA repair genes may contribute to variations in the DNA repair capacity and subsequently susceptibility to cancer.Objectives This study aimed to investigate the association between Excision repair cross-complementation groups 2 (ERCC2) single nucleotide polymorphisms (SNPs rs1799793 and rs13181) and the response to platinum-based chemotherapy among patients with oral squamous cell carcinoma (OSCC).Methodology Polymerase chain reaction‐based restriction fragment length polymorphism analysis was used to determine the polymorphism from a total of 150 OSCC patients and 150 normal tissues of same patients were collected as controls for this study.Results ERCC2 GA (Asp312Asn) AC (Lys751Gln) genotypes were significantly associated (p = 0.0001 and p = 0.0004, respectively) with OSCC patients, when compared with the controls. These findings suggest that potentially functional SNPs in ERCC2 may contribute to OSCC risk. This study highlights the genetic variant that might play a role in mediating susceptibility to OSCC in this population. An understanding of DNA repair gene polymorphisms might not only enable risk assessment, but also response to therapy, which target the DNA repair pathway.
Keywords: oral cancer; ERCC2; DNA repair; platinum-based chemotherapy